PERANCANGAN UI/UX APLIKASI MOBILE TIKET KONSER “EuFo” MENGGUNAKAN METODE DESIGN THINKING - baladiah, dafa sitanala putra (Universitas Lampung, 2024)
EuFo is an app that focuses on the purchase of concert tickets, concert news, promotions, and other information. The distribution process of entertainment content, especially concerts, has been transformed by technological advances in the digital entertainment industry. After conducting User Research, the main problems were age filtering for underage users and user difficulties when entering the venue and also complicated and slow validation of concert tickets. Design applications using the Design Thinking method and analyze application performance results using the Usability Testing method as the goal of research. Design Thinking is an innovative approach to problem-solving that focuses on a thorough understanding of the user, creating creative solutions, and repeating iterations to the best results. The study combines components such as Empathize, Define, Ideate, Prototype, and Test. The results showed that the prototype of the concert ticket application was designed with a one-time iteration of changes and tested to ensure that the UI/UX design results matched the primary purpose. In the first and second tests, there's progress between the one and the two. Results in two tests with fifteen informants resulted in a comparison of the results of two tests: direct success 7%, mission unfinished 0%, misclick rate 5% and duration 10s.